Long-term exposure to fine particulate matter and tachycardia and heart rate: Results from 10 million reproductive-age adults in China. (November 2018) - Xie, Xiaoxu; Wang, Yuanyuan; Yang, Ying; Xu, Jihong; Zhang, Ya; Tang, Wenbin; Guo, Tongjun; Wang, Qiaomei; Shen, Haiping; Zhang, Yiping; Yan, Donghai; Peng, Zuoqi; et al.
Abstract: Background: Epidemiological evidence of the association of long-term ambient fine particulate matter (aerodynamic diameter ≤2.5 μm; PM2.5 ) exposure with resting heart rate is limited. We explored the association of long-term (3-year average) ambient PM2.5 exposure with tachycardia and resting heart rate. Methods: This cross-sectional study surveyed 10, 427, 948 reproductive-age (20–49 years) adults across China in 2015. Tachycardia was classified as a resting heart rate of >80 beats per minute (bpm). The annual average ambient PM2.5 concentrations were obtained from a hybrid satellite-based geophysical statistical model. Linear mixed models and mixed effects logistic regressions adjusted for potential confounding were performed to explore the associations of PM2.5 with resting heart rate and PM2.5 with tachycardia, respectively. The effect modifiers by sex, age, body mass index, urbanity, race, region, smoking status, and drinking status were also assessed. Attributable cases and population fraction were estimated according to the PM2.5 - tachycardia relationship. Results: The mean age was 28 years, and 16.3% of the participants had tachycardia. The odds ratio for tachycardia was 1.018 (95% confidence intervals [CI]: 1.017, 1.020) per 10 μg/m 3 increase in the 3-year average PM2.5 exposure. A 10 μg/m 3 increase in the 3-year average ambient PM2.5 level was associated with a 0.076 (95% CI: 0.073, 0.079) bpm elevation in the resting heart rate. Of the tachycardia burden, 4.0% (95% CI: 3.8%, 4.3%) could be attributed to ambient PM2.5 exposure in Chinese reproductive-age adults. Conclusions: Exposures to ambient PM2.5 were associated with elevated resting heart rate. It might be possible to decrease China's avoidable tachycardia burden in reproductive-age adults through decreasing PM2.5 levels. Graphical abstract: Image 1 Highlights: This is the largest study to evaluate the association between PM2.5 and heart rate. PM2.5 was positively associated with tachycardia and increased heart rate. Of the studied tachycardia cases, 4.0% could be attributable to ambient PM2.5 .